2017
DOI: 10.1016/j.pt.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue: A Safe Haven for Parasites?

Abstract: Adipose tissue (AT) is no longer regarded as an inert lipid storage, but as an important central regulator in energy homeostasis and in immunity. Three parasite species are uniquely associated with AT during part of their life cycle: Trypanosoma cruzi, the causative agent of Chagas disease, Trypanosoma brucei, the cause of African sleeping sickness and Plasmodium spp, the cause of malaria. In the AT, T. cruzi resides inside adipocytes, T. brucei is found in the interstitial spaces between adipocytes, while Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 59 publications
3
75
0
2
Order By: Relevance
“…There is a gap in the understanding of how obesity affects the course of intracellular infections, including parasite infections. In accordance with the negative association between obesity and infectious diseases already described (23,35,36), our study showed that obese mice had higher parasite burden than control mice, failing to control parasite growth. In addition, lesions in obese mice were larger and more ulcerative than the ones observed in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…There is a gap in the understanding of how obesity affects the course of intracellular infections, including parasite infections. In accordance with the negative association between obesity and infectious diseases already described (23,35,36), our study showed that obese mice had higher parasite burden than control mice, failing to control parasite growth. In addition, lesions in obese mice were larger and more ulcerative than the ones observed in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Parasites such as Trypanosoma cruzi , Trypanosoma brucei , and Plasmodium spp. infiltrate adipose tissue and reside in extracellular spaces or directly infect adipocytes of humans or mice, which have been excellently reviewed [5, 6]. A number of studies have described infection of human and murine adipocytes by bacteria including Mycobacterium tuberculosis , Enterococcus faecalis , Staphylococcus aureus, and Rickettsia prowazekii [712].…”
Section: Adipose Tissue: a Reservoir For Diverse Microbesmentioning
confidence: 99%
“…Tryponosoma cruzi also infects adipocytes (specialised cells of adipose tissue) and is capable of consuming stored lipids 48 . It is unclear how T. brucei , an extracellular parasite, accesses lipids that are stored inside adipocytes, which constitute the largest storage of lipids in a mammalian host.…”
Section: Metabolic Adaptations During the Trypanosoma Brucei Lifementioning
confidence: 99%